2012
DOI: 10.1038/onc.2012.356
|View full text |Cite
|
Sign up to set email alerts
|

Gankyrin promotes breast cancer cell metastasis by regulating Rac1 activity

Abstract: Tumor metastasis is responsible for most cancer patients' deaths. Understanding the mechanism of metastasis is crucial for improving the cure rate for cancer. Here, we report that Gankyrin, a chaperone of ubiquitin-proteasome, has an essential role in breast cancer metastasis. We find that Gankyrin is highly overexpressed in human breast cancers and the expression correlates strongly with lymph node metastasis. Knocking down Gankyrin expression in highly metastatic human breast cancer cells significantly decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 38 publications
3
47
0
Order By: Relevance
“…We previously reported that Gankyrin is overexpressed in human lung and breast cancers and plays an essential role in breast cancer metastasis (10,16). To determine the role of Gankyrin in tumor metastasis, we extended our observation to CRC given that Gankyrin promoted cell proliferation and tumor growth in a colon cancer cell line HCT116 as recently reported (33).…”
Section: Elevated Gankyrin Expression In Primary Colorectal Cancers Wmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that Gankyrin is overexpressed in human lung and breast cancers and plays an essential role in breast cancer metastasis (10,16). To determine the role of Gankyrin in tumor metastasis, we extended our observation to CRC given that Gankyrin promoted cell proliferation and tumor growth in a colon cancer cell line HCT116 as recently reported (33).…”
Section: Elevated Gankyrin Expression In Primary Colorectal Cancers Wmentioning
confidence: 99%
“…The siRNAs of Gankyrin and control Photinus pyralis luciferase gene were from Invitrogen, and the target sequences were described previously (10). The Lipofectamine reagent (Invitrogen) was used for transfections, and the final concentration of siRNA was 50 nmol/L.…”
Section: Cell Transfection and Transductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gankyrin is a chaperone of the ubiquitin-proteasome and a novel oncogene, and has been demonstrated to be overexpressed in numerous types of cancer (25)(26)(27), including liver cancer (28)(29)(30), breast cancer (31,32), colorectal cancer (33), estrogen-driven endometrial carcinoma (26) and oral cancer (34). Gankyrin serves an essential role in tumor occurrence and development (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). p115 is a tether protein that has an important role in a number of signaling pathways required for cell proliferation, and has been extensively studied (35,36).…”
Section: Introductionmentioning
confidence: 99%